Nano-elicitation strategy to improve specialized metabolite pathways in plant cell suspension culture - Ashraf, Kamran; uz Zaman, Qamar; Tang, Weihua; Jiang, Pei; Wan, Xun; Yuri, Khitev; Mohsin, Ali; Guo, Meijin (Frontiers in Plant Science, 2025)
Plant hormone-loaded nanoparticles (NPs) represent a novel class of materials with significant potential in plant cell culture, owing to their unique physico-chemical properties. The utilization of these hormone-loaded NPs as elicitors could enhance the production of bioactive compounds and boost antioxidant enzymatic activity in plant cell suspension cultures. Therefore, this study aimed to synthesize jasmonic acid (JA) loaded Fe3O4 NPs and evaluate their effects on the cell suspension culture of Carthamus tinctorius (safflower). The synthesized material was applied at various concentrations (10, 20, 40 and 80 mg L-1) to assess its impact on cell growth, physio-biochemical, antioxidative activities and specialized metabolites (SMs) of C. tinctorius. The results demonstrated that the addition of JA-loaded NPs significantly enhanced the total chlorophyll (70.37%), soluble protein (154.45%) and total phenolic contents (110.64%) of safflower compared to the control. A linear decrease in all reactive oxygen species (ROS) attributes, such as H2O2 (4.65%) and O2- (22.81%), was observed as the NPs concentration in the culture media was increased to the T2 group (20 mg L-1). Maximum chlorogenic acid (CGAs) accumulation (43.76 mg g-1) was noted on 72 hours after elicitation, representing a 2.26-fold increase over the control group. Furthermore, amino acid profiling revealed substantial variations in the composition of all detected amino acids following treatment with JA-loaded Fe3O4 NPs. In summary, this strategy demonstrates potential for optimizing the production of antioxidant and bioactive metabolites, thereby offering a viable solution for the industrial scale production of high-quality safflower extracts.